2020
DOI: 10.3390/jof6040248
|View full text |Cite
|
Sign up to set email alerts
|

Proper Functions of Peroxisomes Are Vital for Pathogenesis of Citrus Brown Spot Disease Caused by Alternaria alternata

Abstract: In addition to the production of a host-selective toxin, the tangerine pathotype of Alternaria alternata must conquer toxic reactive oxygen species (ROS) in order to colonize host plants. The roles of a peroxin 6-coding gene (pex6) implicated in protein import into peroxisomes was functionally characterized to gain a better understanding of molecular mechanisms in ROS resistance and fungal pathogenicity. The peroxisome is a vital organelle involved in metabolisms of fatty acids and hydrogen peroxide in eukaryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…Leaves treated with water, DMSO/EtOH, MeOH, or toxin alone were used as mock controls. wall integrity in Δpex6 might be one of the reasons contributing to its lower viability (Wu et al, 2020a). The current study revealed that the pex6-deficient strain has lower chitin content of cell walls compared to wild-type.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…Leaves treated with water, DMSO/EtOH, MeOH, or toxin alone were used as mock controls. wall integrity in Δpex6 might be one of the reasons contributing to its lower viability (Wu et al, 2020a). The current study revealed that the pex6-deficient strain has lower chitin content of cell walls compared to wild-type.…”
Section: Discussionmentioning
confidence: 53%
“…Keissler used as a recipient host for transformation and mutagenesis experiments was obtained from a diseased citrus leaf and has been previously characterized ( Lin et al, 2009 ). Two pex6 mutant (Δ pex6 ) strains M4 and M9 were independently identified by targeted deletion of the Pex6 gene in wild-type ( Wu et al, 2020a ). The CP4 strain was identified by transforming and expressing a functional copy of Pex6 in Δ pex6 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations